Assessment of the health status of citrus propagation material against Hop stunt viroid through biological and molecular diagnosis (2024)
Hop stunt viroid (HSVd) is the causal agent of citrus cachexia, which can lead to significant crop losses. As part of a preventive management strategy, it is essential to use healthy plants from a certification program. This study aimed to, healthiness of 17 citrus cultivars was evaluated against HSVd using both biological and molecular diagnostics. For biological diagnosis, Etrog citron (Citrus medica L.) clone Arizona 861 S1 was used as an indicator plant, incorporating negative and positive controls for HSVd infection. For molecular diagnosis, reverse transcription polymerase chain reaction (RT-PCR) technique was employed with specific primers for viroid detection. Results indicated that six months after inoculation, the positive control exhibited symptoms associated with viroid infection, such as necrosis in the petiole and stem, leaf epinasty, and necrosis in the midvein. In contrast, both the negative control and evaluated citrus cultivars showed no symptoms. These findings were supported by molecular analysis, which allowed the amplification of a viroid genome region only in the positive control. Both biological and molecular diagnosis confirmed the absence of HSVd in the citrus varieties assessed. This study will facilitate the evaluation of the citrus plant collections used in the foundation category as a source of buds for plant multiplication of registered and certified seeds for citrus propagation nurseries in Colombia.